2019
DOI: 10.2196/10842
|View full text |Cite
|
Sign up to set email alerts
|

Text-Based Illness Monitoring for Detection of Novel Influenza A Virus Infections During an Influenza A (H3N2)v Virus Outbreak in Michigan, 2016: Surveillance and Survey

Abstract: Background Rapid reporting of human infections with novel influenza A viruses accelerates detection of viruses with pandemic potential and implementation of an effective public health response. After detection of human infections with influenza A (H3N2) variant (H3N2v) viruses associated with agricultural fairs during August 2016, the Michigan Department of Health and Human Services worked with the US Centers for Disease Control and Prevention (CDC) to identify infections with variant influenza vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Passive surveillance methods can miss infections, while other active surveillance strategies, like in-person or phone screening, can be very time- and resource-intensive. This evaluation supports the results of the initial study of TIM’s use during a swine flu outbreak at agricultural fairs [ 17 ]. In that use case, TIM successfully identified two cases among the 392 individuals monitored for illness over a 4-week period.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Passive surveillance methods can miss infections, while other active surveillance strategies, like in-person or phone screening, can be very time- and resource-intensive. This evaluation supports the results of the initial study of TIM’s use during a swine flu outbreak at agricultural fairs [ 17 ]. In that use case, TIM successfully identified two cases among the 392 individuals monitored for illness over a 4-week period.…”
Section: Discussionsupporting
confidence: 82%
“…In that use case, TIM successfully identified two cases among the 392 individuals monitored for illness over a 4-week period. Stewart et al [ 17 ] reported that two types of text messages were sent: one using formal language and another using informal language. The informal version was associated with more staff follow-up time due to false alerts and unrecognized text responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technological innovations including software and web platforms, mobile phones, tablets, and applications or “apps” are powerful resources being used to implement surveillance, prevention, control and preparedness activities. For example, in the United States, text-based monitoring has also been used to improve detection of illnesses caused by novel influenza A viruses 41 . More sophisticated smartphone technology has spurred comprehensive surveillance, data collection, and prevention applications.…”
Section: Methodsmentioning
confidence: 99%
“…However, 74% of monitored persons responded to at least one automated message. This number is higher than what has been reported in other studies examining the use of automated monitoring tools for other infectious diseases [18,19]. The majority persons monitored that responded to automated messages did so directly via Sara Alert; suggesting that persons monitored accepted use of a digital tool to report symptoms.…”
Section: Resultsmentioning
confidence: 62%